Urgent‐start peritoneal dialysis versus haemodialysis for people with chronic kidney disease - Htay, Htay (Cochrane Database Syst Rev, 2017)
This is a protocol for a Cochrane Review (Intervention). The objectives are as follows: This review aims to look at the benefits and harms of urgent‐start PD (defined as initiation of PD within 2 weeks of catheter insertion) compared to HD (defined as initiation of HD using a CVC) in adults and children with CKD requiring long‐term RRT.